A microRNA signature in circulating exosomes is superior to exosomal glypican-1 levels for diagnosing pancreatic cancer. (1st May 2017) - Lai, Xianyin; Wang, Mu; McElyea, Samantha Deitz; Sherman, Stuart; House, Michael; Korc, Murray
Abstract: Pancreatic ductal adenocarcinoma (PDAC) is a deadly malignancy that often presents clinically at an advanced stage and that may be confused with chronic pancreatitis (CP). Conversely, CP may be misdiagnosed as PDAC leading to unwarranted pancreas resection. Therefore, early PDAC diagnosis and clear differentiation between PDAC and CP are crucial for improved care. Exosomes are circulating microvesicles whose components can serve as cancer biomarkers. We compared exosomal glypican-1 (GPC1) and microRNA levels in normal control subjects and in patients with PDAC and CP. We report that exosomal GPC1 is not diagnostic for PDAC, whereas high exosomal levels of microRNA-10b, (miR-10b), miR-21, miR-30c, and miR-181a and low miR-let7a readily differentiate PDAC from normal control and CP samples. By contrast with GPC1, elevated exosomal miR levels decreased to normal values within 24 h following PDAC resection. All 29 PDAC cases exhibited significantly elevated exosomal miR-10b and miR-30c levels, whereas 8 cases had normal or slightly increased CA 19-9 levels. Thus, our exosomal miR signature is superior to exosomal GPC1 or plasma CA 19-9 levels in establishing a diagnosis of PDAC and differentiating between PDAC and CP. Highlights: Liquid chromatography-tandem mass spectrometry can quantitate glypican-1 levels. Glypican-1 levels in exosomes are not diagnostic for pancreatic cancer. A microRNA signature in exosomes is diagnostic for pancreatic cancer.